Analisis kemampuan keuangan daerah dan kebijakan Kabupaten Bangka Barat tahun 2004-2007 - ABIMANYU, ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This study on local financial capacity and policy was conducted in West Bangka Regency, the Province of Bangka Belitung Islands. It was to analyze the degree of financial capacity, financial performance, tax effort, tin contribution, and other sources of Local Revenue, and their growth and projection, elasticity, and policy formulation. Data used in the study were primary data, obtained from interviews and questionnaires, and secondary data, those on the Gross Regional Domestic Product (PDRB), population and the realization of the 2004-2007 Local Budget in West Bangka Regency. Analytical instruments were the DOFD, tax efforts, IKKPD, contribution, growth, projection, elasticity, and analysis on public policy. Result of the analysis indicates that the DOFD of West Bangka Regency at a period of 2004-2007 was in a low category of 7.13 percent, while the trend of IKKPD rise after the splitting of region, meaning that the program was successful. While the tax efforts without mining were still low, but a trend always increase up to 0.0061 on 2007 and tax efforts with mining increase up to 0,0052 on 2007. The tin did not yet directly contribute to the Local Revenue. Contribution to the Local Revenue was more from saving’s interest (2.38 percent) of the Total Local Revenue due to large SiLPA. The tin has given a larger contribution to the Transfer Fund of Natural Resources (7.30 percent) and to growth (63.43percent). West Bangka Regency has still large capital to increase the Local Revenue and the elasticity of tax to the PDRB was 2.39 while that of the Local Revenue to the PDRB 1.75 on 2007. It was indicated also by the ratio of the PDRB per capita, i.e. Rp23,606.020,00, while the tax per capita was just Rp47,309.00 or tax per capita only 0,20 percent from PDRB per capita. From the analysis on public policy, alternative policy on the optimization of intensification outcome has a good prospect to apply, indicated by a high score of 18 compared with the other alternative policies. From a result of forecasting, the alternative policy on the optimization of intensification outcome has generated the most additional Local Income of Rp28,981,665,864.74 on 2011 compared with the other alternative policies. However, West Bangka Regency can implement all the proposed alternative policies simultaneously, as appropriate. Based on the analyses, it can be concluded that although the regency has the low levels of DOFD, tax efforts and IKKPD, it has large capital to increase the Local Revenue, indicated by the increased level of elasticity, the PDRB per capita, growth, tax efforts, and IKKPD. Therefore, it can be expected that West Bangka Regency can immediately implement the recommended alternative policy in terms of increasing the Local Revenue. Keywords: Local Financial Capacity, Financial Performance, Fiscal Autonomy, Alternative Policy